2020
DOI: 10.3389/fphys.2020.00537
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Voluntary Ventilation Should Not Be Estimated From the Forced Expiratory Volume in the First Second in Healthy People and COPD Patients

Abstract: Purpose: To evaluate the concordance between the value of the actual maximum voluntary ventilation (MVV) and the estimated value by multiplying the forced expiratory volume in the first second (FEV 1 ) and a different value established in the literature.Methods: A retrospective study was conducted with healthy subjects and patients with stable chronic obstructive pulmonary disease (COPD). Five prediction formulas MVV were used for the comparison with the MVV values. Agreement between MVV measured and MVV obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In many papers on the differences between measured MVV (mMVV) and calculated MVV (cMVV), which is obtained by multiplying the MVV with measured FEV1, a standardized and reproducible maneuver, with an appropriate factor (generally 35 or 40), has been observed to be significant [16,17,19,[21][22][23]37]. Preferences regarding the use of cMVV versus mMVV for ventilator capacity calculation are dependent on the studied cohort: for example, in pediatric populations, cMVV has been shown to be a more accurate surrogate measure of maximum ventilator capacity, most likely due to inadequate effort and inability to perform MVV maneuvers [38].…”
Section: Discussionmentioning
confidence: 99%
“…In many papers on the differences between measured MVV (mMVV) and calculated MVV (cMVV), which is obtained by multiplying the MVV with measured FEV1, a standardized and reproducible maneuver, with an appropriate factor (generally 35 or 40), has been observed to be significant [16,17,19,[21][22][23]37]. Preferences regarding the use of cMVV versus mMVV for ventilator capacity calculation are dependent on the studied cohort: for example, in pediatric populations, cMVV has been shown to be a more accurate surrogate measure of maximum ventilator capacity, most likely due to inadequate effort and inability to perform MVV maneuvers [38].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only one study evaluated maximal voluntary ventilation (MVV) and showed improvement suggesting that this intervention could be effective for this outcome ( 30 ). Although this test measures ventilation, it has been described in the literature as an assessment scale for the endurance of respiratory muscles ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…MVV is the ventilation volume obtained by repeating the maximum spontaneous breathing as fast and as deep as possible in a period of time and is a reliable index for the comprehensive evaluation of the pulmonary ventilation reserve [ 39 , 45 ]. It is related to the strength of the respiratory muscles, the elasticity of the thorax and lung tissue, and airway resistance.…”
Section: Methodsmentioning
confidence: 99%